Are there clinical and neurophysiologic predictive factors for a positive response to HF-rTMS in patients with treatment-resistant depression?. (June 2018) - Poleszczyk, Anna; Rakowicz, Maria; Parnowski, Tadeusz; Antczak, Jakub; Święcicki, Łukasz
Highlights: HF-rTMS was equally effective in treatment-resistant unipolar and bipolar depression. In the total sample containing unipolar and bipolar patients, longer disease duration, higher number of prior psychiatric hospitalizations, and more disturbed activity were associated with a worse response to rTMS treatment. More pronounced somatic anxiety, sleep disorders, and probably more health worries were associated with a better outcome. In the sample limited to bipolar patients, longer disease duration and sleep disturbances retained the predictive value, which was not the case with the other factors mentioned in point 2. In bipolar patients, however, the history of treatment with several psychotropic substances was associated with a worse therapeutic response. Neurophysiologic measurements of cortical excitability showed predictive value only in bipolar patients. Abstract: Better selection of patients with treatment-resistant depression for high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) would make the procedure more efficient. The objective of this study was to search for clinical and neurophysiologic predictors of therapeutic response with a special focus on the bipolar population. Forty patients (30 bipolar) underwent 20 daily sessions of HF-rTMS. Clinical outcome measures included the 21-item Hamilton Depression Rating Scale, the Beck Depression Inventory, the Clinical Global Impression, and the Patient Global Impression. Neurophysiologic measurements included repeated estimation of the motor threshold and cortical silent period. Improvement was obtained in all psychometric scales, with no difference between unipolar and bipolar patients. Longer duration of the illness, higher number of prior hospitalizations, and more disturbed activity were associated with a worse response to rTMS, and somatic anxiety, sleep disorders, and health worries were positive predictors. In bipolar patients, longer disease duration and therapy with mirtazapine, mianserin, trazodone, hydroxyzine, and promethazine were associated with a worse response. Sleep disturbances, higher baseline motor threshold, and longer cortical silent period predicted a better response. In this study, we found several clinical and neurophysiologic predictors of better/worse responses to the standard HF-rTMS protocol. Our preliminary data need to be reproduced.